Tertiary institutions and capacity building in Ghana: challenges and the way forward. Issue 3 (2nd July 2016) - Arthur, Peter; Arthur, Emmanuel
Abstract : The last two decades have seen tremendous growth in tertiary education in Ghana. The prevailing consensus is that universities play a crucial role in development by making it possible to generate human capital in key areas such as health, agriculture, and engineering, also contributing to the attainment self-sufficiency. Whilst contributing to capacity building, this paper argues that universities in Ghana have had to contend with a number of challenges: low female access to universities, especially in science and technology-related courses; inadequate funds; poor research activity; and large class sizes. Making research a priority, designating strategic planning teams with appropriate institutional and financial support, developing cooperation with private universities, expanding access through the use of external degree centres and distance learning, and deepening universities' relevance to societal needs, are identified as central to the enhancement of capacity building in Ghana.